PENGARUH MONEY ETHICS TERHADAP TAX EVASION DENGAN MATERIALISM DAN GENDER SEBAGAI PEMODERASI (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to determine the effect of money ethics on tax evasion, with intrinsic religiosity, materialism and gender as moderating variables. This study uses a survey method and the population is an individual taxpayer who has a NPWP and who is domiciled in Central Java. The data used consists of primary data, which comes from distributing questionnaires to individual taxpayers who have a NPWP and who are domiciled in Central Java and use a 1-7 linkert scale. The data analysis used is stepwise regression analysis. The results of this study are that there is a significant positive effect between money ethics on tax evasion. Materialism is able to weaken the relationship between money ethics and tax evasion. Likewise, gender is able to strengthen the relationship between money ethics and tax evasion. Meanwhile, intrinsic religiosity is not able to moderate the relationship between money ethics and tax evasion.